HUBUNGAN PIJAT OKSITOSIN TERHADAP KELANCARAN PRODUKSI ASI PADA IBU NIFAS DI DESA SUKOHARJO PATI - Amelia Nur Hidayanti; Naomi Parmila Hesti S (Universitas Batam, 2022)
Breastfeeding is a very important thing for a mother to her baby because breast milk has many nutrients that are useful for her intelligence and growth and baby. In Indonesia there are still many babies who have not received good breast milk. Not all postpartum mothers immediately took out breast milk is a very complex between mechanical stimulation, nerves and various hormones that affect oxygens and spending. Oxytocin massage is one of the activities to provide functioning stimulation or massage that functions to stimulate oxyocin hormones in order to facilitate breast milk and increase mother's comfort. Massages performed by massage on the second area of the spine throughout the second side, so that it relaxes can also stimulate the oxization expenditure of oxytocin. The purpose of this observation was to determine the pinjat oxytocin relationship with the smooth production of breast milk in the Niphaas Village in the Sukoharjo Pati Village. This type of observation is an analytic survey and uses a cross sectional method. The population in this observation is postpartum mothers with Stratified Random Sampling technique. The total sampling was 31 respondents.show the Oxytocin Massage Relationship to the Breast Milk Production Mothers Sukoharjo Village in the Sukoharjo Pati Village. With the value of the value of 0.000 <0.05. Based on the observations that have been carried out showed the Oxytocin Massage Relations in Breast Milk Production Mother Nifas In Sukoharjo Pati Village